A Self-Expanding Nitinol Fixation System for Atrial Leadless Pacemakers: Biomechanical Design and Evaluation - Yu-Tzu Wang; Yu-Sheng Lin; Yu-Wei Lin; Chun-Ming Chang; Lung-Sheng Wu; Chao-Sung Lai; Pao-Hsien Chu (Bioengineering)
Atrial leadless pacemakers (ALPMs) offer a minimally invasive solution for patients requiring atrial pacing, but current designs face significant challenges related to fixation stability, perforation risk, and retrievability. This study presents a novel self-expanding nitinol fixation system designed for deployment within the left atrial appendage (LAA), incorporating a flexible adapter for secure pacemaker engagement and retrieval. Finite-element simulations were conducted to assess gravitational displacement across different anatomical orientations, and fixture-expansion behavior was analyzed under various mesh configurations. The pacemaker drop analysis results demonstrated minimal displacement in neutral and upward-tilted LAA models, with increased instability observed in downward-tilted orientations. The fixture-expansion study showed that the 0.2 mm mesh design provided adequate mechanical strength and strain tolerance while maintaining a compact profile. This novel fixation system improves current ALPM limitations by providing stable, retrievable anchoring and favorable biomechanical performance. It may also serve as a dual-function platform for atrial pacing and stroke prevention when integrated with a left atrial appendage (LAA) occluder. These findings support further preclinical validation for clinical translation.